Competencies analysis for future employees to optimize organizational performance - Haque, A. K. M. Ahasanul; Kabir, SMH; Abdullah, Kalthom; Rahman, Mohammad Moshiur; Tarofder, Arun Kumar (Globeedu Group, 2019)
Human resource management as a strategic function looks for different management skills in the candidates during recruitment process. Having management skills in the form of competencies are crucial to optimize organizational performance. Therefore, analysis of competencies is essential for the candidates who will be the future employees to understand the strategic directions of an organization. The objective of this study was to identify the competencies which were required in the future employees by the human resource management to increase performance of an organization. This research has been accomplished by analyzing the application of competencies in candidates who were seeking jobs in Malaysia. A qualitative research method has been chosen by having in-depth interviews of six graduates of business and management studies from Kuala Lumpur. Data has been analyzed systematically using NVivo computer program. The findings of this study revealed that the job seekers are not well aware of the required competencies by the prospective employers. Comfortable job and good working environment were the most desirable preferences of job seekers to ensure their carrier path and overall performance. Professional knowledge and communication skills were the most significant competencies stated by 66% of job seekers. This study can be beneficial to the candidates for preparing themselves more effectively according to the desired competencies by the employers to sustain in the ever-challenging job market in 21st century. The investigation can be carried out with more specific job industry with larger sample size for better results as a scope in future.